LIPID-LOWERING EFFICACY OF ROSUVASTATIN COMPARED WITH OTHER STATINS - A. N. Meshkov (Столичная издательская компания, 2015)
Assessment of lipid-lowering effect of rosuvastatin is presented, as well as the main results of the study of rosuvastatin therapy efficacy , in comparison with other statins, received in controlled clinical trials of the GALAXY program: COMETS, LUNAR, MERCURY-I, SOLAR, STELLAR.